2020
DOI: 10.3389/fphar.2020.00410
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis and Characterization of Micrometric Single Crystalline Magnetite With Superparamagnetic Behavior and Cytocompatibility/Cytotoxicity Assessments

Abstract: A new class of magnetite (Fe 3 O 4) particles, coined as "Single Crystalline Micrometric Iron Oxide Particles" (SCMIOPs), were obtained by hydrothermal synthesis. Both the single Fe 3 O 4 phase content and the particle sizes range, from 1 µm to 30 µm, can be controlled by synthesis. The notable finding states that these particles exhibit vanishing remanent magnetization (sr=0.28 emu/g) and coercive force (Hc=1.5 Oe), which indicate a superparamagnetic-like behavior (unexpected at micrometric particles size), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Our research group has already demonstrated that Fe 3 O 4 nanoparticles are responsible for inducing alterations of amelanotic human A375 cells and murine melanoma B164A5 cells depending on cell phenotype and metastatic activity [ 71 , 72 , 73 ]. However, through the current study, antitumorigenic screening of these nanoparticles extends to breast adenocarcinoma cells, and based on the present data, MCS developed in this study revealed promising potential as a hyperthermia-inducing tool in the biological environment.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has already demonstrated that Fe 3 O 4 nanoparticles are responsible for inducing alterations of amelanotic human A375 cells and murine melanoma B164A5 cells depending on cell phenotype and metastatic activity [ 71 , 72 , 73 ]. However, through the current study, antitumorigenic screening of these nanoparticles extends to breast adenocarcinoma cells, and based on the present data, MCS developed in this study revealed promising potential as a hyperthermia-inducing tool in the biological environment.…”
Section: Discussionmentioning
confidence: 99%
“…Our group already reported that MIONPs are cytotoxic against tumor melanoma cells, generating different responses depending on the cell origin, phenotype and metastatic potential. [72][73][74] The stronger BA cytotoxic effect on MDA-MB-231 cells versus MCF7 cells could explain the difference in cell viability percentages induced by the BA-loaded nanoplatforms when applied on the two breast adenocarcinoma cell lines. In terms of hyperthermia effects, it could be noticed a decrease in the MDA-MB -231 cell population when treated with BA-loaded nanoformulations, compared to the same treatment groups under normothermic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…MTT assay. Cell viability was evaluated by using the MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) kit (Roche, Mannheim, Germany) according to the experimental protocol described in our previous studies [ 59 ]. In brief, HaCaT and A375 cells (1 × 10 4 /200 μL medium/well) were seeded in 96-well plates and stimulated with increasing concentrations (0–50 µM) of BA solubilized in DMSO for 24 h. The plates were incubated for 3 h at 37 °C with 10 µL/well of MTT reagent, followed by addition of buffer solution (100 µL/well) and incubation at room temperature and dark for 30 min.…”
Section: Methodsmentioning
confidence: 99%